Der größte lateinische Panegyricus: das jesuitische Festbuch zur böhmischen Krönung des Kaisers Karl VI. (1723) – mit einem Exkurs über Carmina cabalistica - Ludwig, Walther (Neulateinisches Jahrbuch, 2020)
Abstract The Jesuits of Bohemia put together a commemorative volume for the coronation of the Emperor Karl VI as King of Bohemia in 1723. It is the most extensive and complex Latin panegyric known so far, containing 288 pages in folio with various Latin, Greek and Hebrew texts, an engraved title page and 13 emblematic pictures. Despite the volume’s significance, its artistic, historical and literary aspects still await a thorough investigation. The dominant and unifying allegory representing Karl VI is the “Fons inexhaustus” (the title begins with these words), which continously produces life-giving water. The volume consists of thirteen parts, each of a similar structure, for which the thirteen Jesuit colleges of Bohemia seem to have been respectively responsible. Each part opens with engravings, followed by oratorical prose, Inscriptiones lapidariae, lyrics in classical and in new metrical compositions, epics, and “versus cabalistici”, which all receive exemplary interpretations in this article. The epic relating the conquest of Belgrad ends with a prophecy of Karl VI becoming king of the Holy Land and of the House of Austria occupying the throne of Constantinople.